Water distribution rules and water distribution performance: a case study in the Tambraparani Irrigation System - Brewer, J.D.; Sakthivadivel, Ramaswamy; Raju, K.V. (International Irrigation Management Institute, 1997)
Explores the relationship of water distribution rules to water distribution performance in the Tambraparani Irrigation System in India. Argues that if water distribution rules do not match the irrigation services desired by the users, the users subvert the rules to provide the water deliveries they require, with negative impacts on water distribution performance and equity, and the cost of irrigation.